Information at Your Fingertips: Use of the Internet at the Life Sciences Reference Desk - Janet Hughes (Issues in Science and Technology Librarianship)
This paper discusses how, when, and why the Internet has been used at a Life Sciences Reference Desk, and gives examples of some of the resources frequently used at the Life Sciences Reference Desk. Most of the examples are text-based, however, if web versions are also available, the URLs for such sites will be included.